Therapeutic effects on cancer of the active ingredients in rhizoma paridis - Li, Jie; Jia, Jinhao; Zhu, Weiwei; Chen, Jianfei; Zheng, Qiusheng; Li, Defang (Frontiers in Pharmacology, 2023)
Cancer is a major threat to human health, with high mortality and a low cure rate, continuously challenging public health worldwide. Extensive clinical application of traditional Chinese medicine (TCM) for patients with poor outcomes of radiotherapy and chemotherapy provides a new direction in anticancer therapy. Anticancer mechanisms of the active ingredients in TCM have also been extensively studied in the medical field. As a type of TCM against cancer, Rhizoma Paridis (Chinese name: Chonglou) has important antitumor effects in clinical application. The main active ingredients of Rhizoma Paridis (e.g., total saponins, polyphyllin I, polyphyllin II, polyphyllin VI, and polyphyllin VII) have shown strong antitumor activities in various cancers, such as breast cancer, lung cancer, colorectal cancer, hepatocellular carcinoma (HCC), and gastric cancer. Rhizoma Paridis also has low concentrations of certain other active ingredients with antitumor effects, such as saponins polyphyllin E, polyphyllin H, Paris polyphylla-22, gracillin, and formosanin-C. Many pharmacists have studied the anticancer mechanism of Rhizoma Paridis and its active ingredients. This review article describes research progress regarding the molecular mechanism and antitumor effects of the active ingredients in Rhizoma Paridis, suggesting that various active ingredients in Rhizoma Paridis may be potentially therapeutic against cancer.